Impaired systemic tetrahydrobiopterin bioavailability and increased dihydrobiopterin in adult falciparum malaria: association with disease severity, impaired microvascular function and increased endothelial activation. - Tsin W Yeo; Daniel A Lampah; Enny Kenangalem; Emiliana Tjitra; Ric N Price; J Brice Weinberg; Keith Hyland; Donald L Granger; Nicholas M Anstey (PLoS Pathogens)
Tetrahydrobiopterin (BH₄) is a co-factor required for catalytic activity of nitric oxide synthase (NOS) and amino acid-monooxygenases, including phenylalanine hydroxylase. BH4 is unstable: during oxidative stress it is non-enzymatically oxidized to dihydrobiopterin (BH₂), which inhibits NOS. Depending on BH₄ availability, NOS oscillates between NO synthase and NADPH oxidase: as the BH₄/BH₂ ratio decreases, NO production falls and is replaced by superoxide. In African children and Asian adults with severe malaria, NO bioavailability decreases and plasma phenylalanine increases, together suggesting possible BH₄ deficiency. The primary three biopterin metabolites (BH₄, BH₂ and B₀ [biopterin]) and their association with disease severity have not been assessed in falciparum malaria. We measured pterin metabolites in urine of adults with severe falciparum malaria (SM; n=12), moderately-severe malaria (MSM, n=17), severe sepsis (SS; n=5) and healthy subjects (HC; n=20) as controls. In SM, urinary BH₄ was decreased (median 0.16 ¼mol/mmol creatinine) compared to MSM (median 0.27), SS (median 0.54), and HC (median 0.34)]; p<0.001. Conversely, BH₂ was increased in SM (median 0.91 ¼mol/mmol creatinine), compared to MSM (median 0.67), SS (median 0.39), and HC (median 0.52); p<0.001, suggesting increased oxidative stress and insufficient recycling of BH2 back to BH4 in severe malaria. Overall, the median BH₄/BH₂ ratio was lowest in SM [0.18 (IQR: 0.04-0.32)] compared to MSM (0.45, IQR 0.27-61), SS (1.03; IQR 0.54-2.38) and controls (0.66; IQR 0.43-1.07); p<0.001. In malaria, a lower BH₄/BH₂ ratio correlated with decreased microvascular reactivity (r=0.41; p=0.03) and increased ICAM-1 (r=-0.52; p=0.005). Decreased BH4 and increased BH₂ in severe malaria (but not in severe sepsis) uncouples NOS, leading to impaired NO bioavailability and potentially increased oxidative stress. Adjunctive therapy to regenerate BH4 may have a role in improving NO bioavailability and microvascular perfusion in severe falciparum malaria.